2019
DOI: 10.1016/j.matchemphys.2019.03.075
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependent conductivity mechanisms observed in Pr2NiTiO6

Abstract: The crossover between two different conduction mechanisms (variable range and small polaron hoppings) is probed utilizing a conjunction of thermally varying conductivity and impedance in polycrystalline Pr2NiTiO6 (PNT). A combination of X-ray diffraction (XRD) and Raman spectroscopic investigations authenticates the lower symmetric monoclinic structure for PNT. The conductivity, impedance and relaxation spectra highlight the combined contributions of the electrodes, grain-boundaries and grain microstructures t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 50 publications
(60 reference statements)
1
6
0
Order By: Relevance
“…With the increasing frequency, after a certain value of frequency, the dipoles lag behind the applied field and do not respond with the field, resulting in a sudden drop in the value of ε'. The maximum value of tanδ is around 0.4 -0.5 for GBs and 0.2 -0.25 for Gs, as described by other researchers [20,42].…”
Section: E) Dielectric Relaxationsupporting
confidence: 78%
See 2 more Smart Citations
“…With the increasing frequency, after a certain value of frequency, the dipoles lag behind the applied field and do not respond with the field, resulting in a sudden drop in the value of ε'. The maximum value of tanδ is around 0.4 -0.5 for GBs and 0.2 -0.25 for Gs, as described by other researchers [20,42].…”
Section: E) Dielectric Relaxationsupporting
confidence: 78%
“…To determine the hopping model involved in the system, we plotted the 𝜎 𝑑𝑐 values against the inverse of temperature (10 3 /T) in the inset of Figure 9(b). The linear trend of the curve indicates the activation of the nearest neighbor hopping model at high-temperature regions [61,62]. The activation energy value was calculated as 0.308 eV using Equation 8.…”
Section: Conductivity Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Based on this background, we found that the RE 2 NiTiO 6 compounds containing light RE ions have unique properties in the areas of optics, electricity and magnetism through the results of the relevant literatures [37][38][39]. However, there are few reports on the RE 2 NiTiO 6 compounds containing heavy RE ions to date, especially in term of the magnetic and MCE properties.…”
Section: Introductionmentioning
confidence: 94%
“…Mechanisms that are commonly utilised to elucidate the AC conductivity properties of perovskites related to the variation in s at different temperatures. For instance, variable range hopping (VRH), small polaron hopping (SPH), quantum mechanical tunnelling (QMT), non-overlapping small polaron tunnelling (NSPT), and overlapping large polaron tunnelling (OLPT) mechanisms [18,[41][42][43][44][45][46]. According to the pattern in Figure 8b, a variation in s values from 298 K to 323 K could be linked to NSPT or SPH.…”
Section: Resultsmentioning
confidence: 97%